The effect of granular material on stress state transducer - D Thungsotanon; C Kulketwong (My University, 2018)
Soil compaction is one of the serious problems in crop production. It occurs under stress conditions in soil, which are induced by agricultural machines. Therefore, it is necessary to characterize stress in the soil so as to predict soil compaction. A stress state transducer is a device used to derive the stresses in the soil. The purpose of this laboratory work was to study the effect of granular material, as a medium, on the static stress that occurs in each plane of the stress state transducer (σx, σy, σz, σn1, σn2 and σn3). In the experimental test, a stress state transducer was placed inside dry sand with different granular sizes, then vertical pressure loading and unloading processes were applied to a range of 0-200 kPa. The z-direction stress was compared with the reference pressure and the results found that grade I sand gave a quite linear relationship between applied load as the equation σz = 0.747Pref + 16.5249, R2 = 0.9866 and corresponding stress on the loading process. In the unloaded case, the pressure was higher than when load testing and had a hysteresis of 15.7305 %. The relationship of stresses in the other planes was similar. A comparable tendency was observed in the larger granular sizes of sand, but with less linearity.
Keywords: Hysteresis; Soil Compaction; Overburden pressure; Soil Management and Crop Yield